HUBUNGAN STATUS SPIRITUAL DENGAN KUALITAS HIDUP PADA LANSIA - Mira Afnesta Yuzefo; Febriana ' Sabrian; Riri ' Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research is to identify the correlation of spiritual states and quality of life in the elderly. The research uses descriptive correlation design with cross sectional approach. The sampling technique is cluster sampling where respondents selected based on inclusion criteria. The research uses the questionnaires as instrument that have already been tested for validity and reliability. This research uses univariate analysis with frequency distribution and bivariate analysis with chi squre test. The results show that the respondents with high spiritual states and  have good quality of life are 32 respondents (33%) and 19 respondents (19,6%) show bad quality of life. The result for respondents who have low spiritual states and good quality of  life are 18 respondents (18,6%) and 28 respondents (28,9%) show bad quality of life. The result of statistic test with chi square test show p value = 0,02 < α = 0,05. It is concluded that there is significant correlation between spiritual states and quality of life. Based on the result of this study, it is suggested to family to care for elderly people and give optimal support elderly to increase quality of life of elderly. Keywords: elderly, spiritual states, spiritual health, quality of life, WHOQOL-BREF